ChemInform Abstract: Enantioselective Synthesis of 3‐Arylquinazolin‐4(3H)‐ones via Peptide‐Catalyzed Atroposelective Bromination. Issue 10 (February 2016) - Diener, Matthew E.; Metrano, Anthony J.; Kusano, Shuhei; Miller, Scott J.
Abstract: A tertiary amine‐containing β‐turn peptide is developed and used as catalyst for the atroposelective bromination of various quinazolinones with high levels of enantioinduction.